Effects of L-Leucine Supplement on The Growth Performance and Carcass Characteristics of Grower- Finisher Broilers Fed With Varying Levels of Protein and Energy - Kusniadi, Edi Erwan (2009)
Four studies were conducted to determine the effects L-leucine supplementation on the growth performance and carcass characteristics of grower-finisher chickens fed diets containing different levels of crude protein (CP) and metabolizable energy (ME). Experiment 1 utilized a series of 4 diets that were formulated to contain ME levels (3200 Kcal/kg or 3000 Kcal/kg) and supplemented with two levels of Lleucine either 0 or 0.5%. In Exp. 1, 80 Cobb broilers were used to examine the effect of L-leucine supplementation on growth performance and carcass characteristics fed different levels of energy. There was no interaction between the dietary levels of L-leucine and ME. The supplementation 0.5% of L-leucine had no significant effect on FI, WG and FCR but significant increased in carcass weight up to 9% was observed. The decrease in ME from 3200 to 3000 kcal/kg also did not affect FI and FCR, but WG decreased up to 7.4%. Similarly, reducing ME had no significant effect on carcass composition and sensory characteristics. Exp. 2, The effect of the growth performance and sensory characteristics in reducing CP supplemented by L-leucine. A series of 6 diets that were formulated to contain CP levels of 20 and 18% at each of three levels of L-leucine supplementation (0, 0.5 and 0.67%). Treatments were applied to Cobb 180 broilers distributed across 36 floor pens with 5 chicks per pen while the parameters measured and procedures were similar to experiment 1. There was no interaction between the level of L-leucine supplementation and CP levels. FI, WG and FCR were not affected with increasing levels of L-leucine supplementation. Breast meat yield in numerically increased when added by L-leucine to a level of 0.5%. However a significant decrease of breast meat obtained when added with L-leucine to a level reached 0.67%. Similarly, the sensory analysis indicated no significant differences in tenderness, juiciness, flavor, aroma, and overall acceptability. Bone and lean were not affected with increasing levels of L-leucine supplementation. Fat was decreased (P<0.05), when leucine was added at 0.5%.